Detection of human cytomegalovirus antigenaemia: a rapid diagnostic technique for predicting cytomegalovirus infection/pneumonitis in lung and heart transplant recipients. Issue 1 (January 1995) - Egan, J J; Barber, L; Lomax, J; Fox, A; Yonan, N; Rahman, A N; Campbell, C S; Deiraniya, A K; Carroll, K B; Craske, J
Abstract : BACKGROUND–New rapid diagnostic techniques offer the opportunity of early diagnosis of human cytomegalovirus (CMV) infection in immunocompromised patients at risk of developing CMV disease. The use of human CMV antigenaemia as a predictor of clinical CMV infection and disease in lung and heart transplant recipients was studied prospectively. METHODS–Twenty three heart and nine lung transplant recipients who survived 40 days were observed by standard CMV surveillance with serological testing, culture, and by sequential testing for CMV antigenaemia. CMV antigenaemia testing is a rapid and quantifiable technique in which a viral lower matrix protein is detected in cytospin preparations of peripheral blood polymorphonuclear leucocytes (PMNLs) by immunofluorescent staining. RESULTS–Eleven patients developed CMV infection and five developed CMV disease (four pneumonitis, one duodenitis). These clinical events occurred at a median of 65 days following transplantation. CMV antigenaemia occurred in 17 patients at a median of 35 days following transplantation. Detection of CMV antigenaemia had a sensitivity of 100%, a specificity of 93.7%, and a positive predictive value of 94.1% for CMV related illness. CMV antigenaemia was positive at a significant interval before the clinical event. High levels of CMV antigenaemia (> 50 CMV antigen positive cells/2 x 10(5) PMNLs) occurred in 11 patients and five of these developed disease. CMV antigenaemia of > 50 CMV antigen positive cells/2 x 10(5) PMNLs had a positive predictive value of 45.5% for disease but a negative predictive value of 100%. Patients with disease had higher levels of antigenaemia than those without disease. CONCLUSIONS–CMV antigenaemia is a rapid diagnostic technique which can identify patients likely to develop CMV disease, potentially allowing early treatment.